Board gender diversity and CSR performance: A French study - Oumaima Benaguid; Hicham Sbai; Hicham Meghouar; Oumaima Antari (Cogent Business & Management, 2023)
The current paper examines how gender diversity influences the corporate social responsibility (CSR) performance of French companies. Specifically, we investigate the impact of certain attributes of female directors, such as their age, education, and nationality, on CSR performance. To analyze this, we utilize the generalized method of moments (GMM) on a sample of 53 French firms listed on the SBF 120 index over the period 2008-2017. The findings reveal a positive association between the presence of women on the board and CSR performance. Furthermore, we discover that the age of female directors has a significant and positive effect on CSR performance. Additionally, the existence of a CSR committee is found to have a significant and positive influence on CSR. However, our study does not find any correlation between the education and nationality of female directors and CSR performance.
Keywords: 650; age diversity; CSR performance; education diversity; gender diversity; nationality diversity